The Effect of Folic Acid Supplementation on Fetal Development: A Study on Prenatal Health and Neural Tube Defect Prevention - Daevy, Chantrea; Reaksmey, Reaksmey (International Journal on ObGyn and Health Sciences, 2025)
Folic acid plays a crucial role in fetal development, particularly in the formation of the neural tube during early pregnancy. Deficiency of this essential B-vitamin has been strongly associated with serious birth defects such as spina bifida and anencephaly. Despite widespread recommendations, gaps in awareness and access to supplementation remain in many regions. This study aims to examine the effect of folic acid supplementation on fetal development outcomes, with a focus on the prevention of neural tube defects and other related birth outcomes such as birth weight and gestational age. A quantitative comparative study was conducted involving 300 pregnant women, divided into two groups: those who regularly consumed folic acid supplements (400 mcg daily) and those who did not or took them irregularly. Data were collected through medical records and structured interviews, and analyzed using statistical methods to identify significant differences in fetal development outcomes between the two groups.The study found that folic acid supplementation was significantly associated with a reduction in neural tube defects, with no cases recorded in the supplemented group compared to 2.5% in the non-supplemented group. Supplementation was also linked to higher average birth weight, longer gestational age, and better Apgar scores. These outcomes remained significant even after adjusting for confounding factors. Folic acid supplementation, particularly when initiated before conception and continued through the first trimester, plays a vital role in preventing neural tube defects and supporting overall fetal health. These findings highlight the importance of early education, routine supplementation, and supportive public health policies to ensure that all women of reproductive age have access to this critical nutrient.